2020
DOI: 10.1038/s41538-020-00079-8
|View full text |Cite
|
Sign up to set email alerts
|

Oiling-out effect improves the efficiency of extracting aroma compounds from edible oil

Abstract: Volatile compounds in foods are a significant factor that affects food intake and preference. However, volatile components in edible oils are poorly understood due to a strong matrix effect. In this study, we developed a method of extracting volatile compounds from extra virgin coconut oil (EVCO) by means of oiling-out assisted liquid-liquid extraction (OA-LLE). Consequently, 44 aroma compounds were isolated and identified from only 5 g of EVCO. Various aroma compounds were detected in addition to δ-lactones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Our previous study showed that OA-LLE is a powerful tool for isolating volatile compounds from edible oils. 11 The extraction procedure for OA-LLE is shown in Fig. 1 (black arrows).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study showed that OA-LLE is a powerful tool for isolating volatile compounds from edible oils. 11 The extraction procedure for OA-LLE is shown in Fig. 1 (black arrows).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the native profile of aroma compounds in edible oil, we proposed OA-LLE in a previous paper 11 . However, some edible oils contain a relatively large amount of non-volatiles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations